2011
DOI: 10.1017/s0007114511001383
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of alkylresorcinol metabolites in human urine

Abstract: Wholegrain cereals are reported to promote beneficial health effects. Wholegrain wheat and rye are almost exclusive sources of alkylresorcinols, and intact alkylresorcinols together with their plasma and urinary metabolites, 3-(3,5-dihydroxyphenyl)-1-propanoic acid (DHPPA) and 3,5-dihydroxybenzoic acid (DHBA), have been proposed as biomarkers of the intake of these foods in humans. The pharmacokinetics of alkylresorcinols and their metabolites in plasma have been determined but not that of the urinary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
4
28
1
Order By: Relevance
“…A previous study showed that AR metabolites excretion is lower during the night: DHPPA and DHBA excretion rates in overnight urine were found to be lower than in day urine in healthy participants (16). We also found that participants of the PC group had significantly greater concentrations of DHPPA and DHBA in 12-h overnight urine than in 12-h day urine.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A previous study showed that AR metabolites excretion is lower during the night: DHPPA and DHBA excretion rates in overnight urine were found to be lower than in day urine in healthy participants (16). We also found that participants of the PC group had significantly greater concentrations of DHPPA and DHBA in 12-h overnight urine than in 12-h day urine.…”
Section: Discussionsupporting
confidence: 63%
“…Both free and conjugated forms (glucuronide or sulfate) of the metabolites are present in urine and plasma. DHPPA usually peaks first in urine and later in plasma (13,16), while DHBA peaks simultaneously in urine and plasma. DHPPA peaking earlier in urine than in plasma could presumably be explained by its higher glucuronization rate than that for DHBA, as reported recently (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, 2 main metabolites of AR 3,5-dihydroxybenzoic acid (DHBA) and 3-(3,5-dihydroxyphenyl)-1-propionic acid (DHPPA) showed longer apparent half-lives compared with intact AR homologs (16,17). The longest apparent half-life was observed for DHPPA (12 h), suggesting that it may better reflect more long-term WG intake (17).…”
Section: Introductionmentioning
confidence: 99%